CONNECTION RELATIONSHIP SEBAGAI MEDIASI PENGARUH MODAL TERHADAP KEWIRAUSAHAAN MAHASISWA - arsyad, dani; Safira, Anggun; Sopingi, Imam; Musfiroh, Anita (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2025)
This study examines the role of connection relationships as a mediating variable in the influence of capital on student entrepreneurship. The capital in question includes financial and social capital, where social relationships function as a bridge to access opportunities and resources that support entrepreneurship. With a quantitative approach through a survey of student entrepreneurs, the results show that connection relationships strengthen the influence of capital on entrepreneurial development. This finding emphasizes the importance of social networks in facilitating the success of student entrepreneurship. This study aims to analyze the role of connection relationships as a mediator of the influence of capital on student entrepreneurship. Entrepreneurship among students is an important issue in the development of the creative economy, where capital plays a major role in influencing business success. However, in addition to financial capital, the connections owned by students also have great potential to support the development of their businesses. This study uses a quantitative approach by collecting data through a survey of students involved in entrepreneurial activities. The results of the analysis show that capital, both financial and social, has a significant influence on student entrepreneurship. In addition, connection relationships have been shown to mediate the influence of capital on the development of student businesses. These findings indicate that strengthening social networks and business relationships can increase the effectiveness of capital use in entrepreneurship.